BiOCl/BiOBr Heterojunction with Rich Oxygen Vacancies Induced by Ultraviolet and Its Enhanced Photocatalytic Performance. Issue 46 (28th November 2019) - Liu, Guoguan; Xu, Haiming; Li, Dongya; Zou, Zhongwei; Li, Qiang; Xia, Dongsheng
Abstract : Novel BiOCl/BiOBr heterojunction with rich oxygen vacancies (OVs) was successfully synthesized via ultrasound and photoinduced method. The XRD, SEM, TEM, XPS, DRS, ESR, SPV, PL, contact angle and electrochemical technique were implemented to characterize the as‐synthesized samples. The experiment results demonstrated that BOCBuv can degrade carbamazepine (2.5 mg/L) by nearly 60 % during 180 min under visible light irradiation, which is 2, 3, 7 times higher than that of BOCB, BOC and BOB, respectively. Furthermore, the presence of OVs and heterojunction structure not only enhance the light absorption but also improve the spatial separation and migration of photogenerated carriers, and thus BOCBuv exhibits polish photocatalytic performance. This research provides a new approach and insight for developing novel efficiency photocatalysts by tailoring surface defects and heterojunction structure. Abstract : BiOCl/BiOBr heterojunction nanocomposites were synthesized by use of ultrasound and light. As the photoinduced oxygen vacancies and the heterojunction from the coupling between BiOCl and BiOBr enhances light absorption performance as well as dramatically accelerating the spatial separation of the photogenerated charge carriers, the resulting BiOCl/BiOBr exhibited outstanding properties.